Twelve weeks of endurance exercise training does not affect iron status measures in women - Bourque, S. P.; Pate, R. R.; Branch, J. D. (Journal of the American Dietetic Association, 1997)
Study design Thirty-one healthy, inactive women (aged 23 to 43 years) were recruited for this randomised, experimental study. Apparently normal iron status (serum ferritin levels >, = 20 ug/L), regular menstrual cycles, regular intake of animal products, BMI of 18 to 30, no regular exercise for past 12 months, no regular donation of blood, and no regular use of medicines that affect blood coagulation and iron status, were used as inclusion criteria. After screening, the subjects were matched for serum ferritin levels and randomly assigned to 3 groups: the inactive control group (n-7), a walking/running group (n = 8) and a cycling group (n = 6). Iron status and haematological parameters were measured at baseline and weeks 2, 4, 8, and 12. All the subjects performed a maximal aerobic power test (Vo2 ) at baseline and after 12 weeks. Subjects in the 2 active groups exercised 3-4 times per week at 80% of initial Vo2 max for the 12 weeks period. Anthropometric measures were recorded at baseline and every 2 weeks. Results The following results were obtained: * in the active groups, energy expenditure increased from 150 kcal/session during week one, to 375 kcal/session in weeks 9 to 12 * analysis of variance showed that mean serum ferritin concentrations did not change significantly in the 12 weeks in either of the 2 active groups (walking/running: from 41.28 to 27.41 ug/L; cycling group: from 65.81 to 41.06 ug/L; control group: from 47.55 to 31.56 ug/L)(P=0.59) * no significant changes in the other iron status parameters (serum iron, total iron-binding capacity, % saturation of transferrin and haptoglobin) were observed (P>0.30), in either of the 2 active groups compared to the control group * no difference in weight-bearing vs non-weight bearing exercise was found * no changes in BMI were found in any of the groups Conclusion The suggestion that long-term exercise depletes iron stores in women and that weight-bearing endurance exercise has a more pronounced effect, could not be substantiated in this study. The authors conclude that, "participation in 12 weeks of moderate-intensity endurance exercise training (walking/running or cycling) is not associated with negative effects on selected measures of iron status in healthy, previously untrained women with normal iron stores (serum ferritin >,=20 ug/L)". It would appear that iron status in healthy women is thus not affected by the type of training that is consistent with current health recommendations.